TENDENCIES AND ART TECHNIQUES IN CONTEMPORARY COMIC BOOK GRAPHIC DESIGN - Kolisnyk, O. V.; Ocheretna, L. V.; Yakovlev, M. I.; Kolosnichenko, O. V.; Pashkevich, K. L.; Kretova, O. M. (Art and Design, 2020)
Purpose. Exploring of the distinctive features of modern comics, their artistic and compositional solutions, types, main trends in American, European and Asian culture. Definition of the original formation of modern Ukrainian comics. Methodology. The basis of the research methodology includes integrated use of historical and comparative methods, system analysis, synthesis, generalization. Results. Basing on the analysis of modern comic book content, the history of comics and its perception by the audience as a modern media text are revealed, characteristics of individual elements in comics are systematized. The specifics of the artistic and compositional system of modern comics, the nature of figurative and stylistic techniques, graphic features of American, European, Asian, Ukrainian comics are determined. Patterns which are inherent in comics as visual narratives of different socio-cultural parts of the world, as well as aspects that shape modern Ukrainian comics, are considered. Scientific novelty. Characteristics of comics as an object of graphic design are determined: features of artistic and compositional design solutions in different regions of the world are systematized; leading trends in the development of specific types of comics in the United States, Europe, Asia and Ukraine are revealed. Practical significance. Based on art analysis of comic book types and by identifying trends in their development within modern art the specifics of the further development of comics are determined and ideas for future creative projects are presented, features that have both artistic and commercial value are indicated.